1997
DOI: 10.1073/pnas.94.13.6792
|View full text |Cite
|
Sign up to set email alerts
|

Defensive production of formic acid (80%) by a carabid beetle ( Galerita lecontei )

Abstract: The carabid beetle Galerita lecontei has a pair of abdominal defensive glands that secrete a mixture of formic acid, acetic acid, and lipophilic components (long-chain hydrocarbons and esters). Formic acid, at the concentration of 80%, is the principal constituent. The beetle ejects the secretion as a spray, which it aims accurately toward parts of the body subjected to assault. At full capacity, the glands store 4.5 mg of formic acid (3% of body mass), enough for upward of six ejections. The beetle reloads th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
2
35
2
Order By: Relevance
“…Their evolution and maintenance is tightly tied to predation avoidance, and this defense is probably one of the major contributing factors to the success of Carabidae (Erwin, 1985;Will et al, 2000). The spray emitted by a beetle in response to predation is directional and unilateral (Rossini et al, 1997). Therefore, the glands are nonredundant: each works to protect its respective side.…”
Section: Why Testes Are Lostmentioning
confidence: 99%
“…Their evolution and maintenance is tightly tied to predation avoidance, and this defense is probably one of the major contributing factors to the success of Carabidae (Erwin, 1985;Will et al, 2000). The spray emitted by a beetle in response to predation is directional and unilateral (Rossini et al, 1997). Therefore, the glands are nonredundant: each works to protect its respective side.…”
Section: Why Testes Are Lostmentioning
confidence: 99%
“…Not surprisingly, many carabids have the capacity to aim their spray in different directions (5)(6)(7)(8)(9). None are perhaps better marksmen than the so-called bombardier beetles, as we document here photographically for one species, the African Stenaptinus insignis.…”
mentioning
confidence: 86%
“…Diverse toxicants are produced by these glands, often at high concentrations, including acids, aldehydes, phenols, and quinones (2,3). Most carabids are able to eject these fluids forcibly, in the form of sprays (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aldehyde (E)-2-decenal was identified as adefensive compound of the staphylinid Omaliinae and Proteininae (Dettner and Reissenweber, 1991 ), meanwhile nonane, decane and octane were detected from the carabid beetle Galerita lecontei abdominal defensive glands (Rossini et al, 1997). Bartelt et al (1993) found that males of the coleopteran Carpophilus antiquus emit E-E-E-E-6-8-diethyl-4-methyl-3-5-7-9-dodecatetraene as aggregation pheromone, (Z)-3-decen-1-ol was recognized from male long-horned cerambycid beetle Rosalia funebris (Ray et al, 2009) and 6-10-13-trimethyl-tetradecan-1-ol was confirmed from the stink bug, Stiretrus anchorago (Kochansky et al, 1989) as well.…”
Section: Chemicals Identified In Different Insect Orders Except Lepidmentioning
confidence: 99%